Immunoembolization for the Treatment of Uveal Melanoma Hepatic Metastases - Gonsalves, Carin F. (Seminars in Interventional Radiology, 2024)
Uveal melanoma is the most common primary intraocular tumor in adults. Approximately 50% of patients develop metastatic disease despite successful treatment of the primary eye tumor. The liver is the most common site of metastatic disease occurring in more than 90% of patients. Clinical prognosis is dependent on the ability to control the growth of liver tumors. Locoregional therapies play an important role in stabilizing liver metastases, prolonging survival for patients with metastatic uveal melanoma. As overall survival is prolonged, the development of extrahepatic disease becomes more common. Immunoembolization, a form of liver-directed therapy, not only focuses on treating hepatic metastases by stimulating the local immune system to suppress the growth of liver tumors, but it potentially generates a systemic immune response delaying the growth of extrahepatic metastases as well. The following article discusses immunoembolization for the treatment of metastatic uveal melanoma including the rationale, mechanism of action, indications, contraindications, outcomes, and associated toxicities.
Keywords: uveal melanoma; immunoembolization; granulocyte macrophage-colony-stimulating factor; liver-directed therapy; interventional radiology